Heat-reflecting heat-insulating coating and preparation method thereof
By using titanium dioxide-loaded cellulose aerogel and dopamine triazine modified nanocellulose in polyurethane coatings, combined with rutile nanotitanium dioxide and ammonium polyphosphate, the poor insulation and insufficient flame retardancy of polyurethane coatings are solved. Problem, higher thermal reflection insulation and flame retardant performance are achieved.
Patent Information
- Application Number
- CN202411320745.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-09-23
AI Technical Summary
Polyurethane coatings have poor thermal insulation performance and insufficient flame retardancy.
Using titanium dioxide-loaded cellulose aerogel, nanocellulose is oxidized by sodium periodate and reacted with dopamine-4,6-diamino-1,3,5-triazine to form dopamine triazine-modified nanocellulose, combined with rutile nanotitanium dioxide and ammonium polyphosphate form an expanded flame retardant system, which improves the thermal reflectivity and flame retardant properties of the coating.
The thermal reflectivity and thermal reflectivity of the coating are significantly improved, the thermal conductivity is reduced, the flame retardant performance is enhanced, and the thermal insulation coating with lower peak combustion heat release rate and total heat release amount is formed.
Smart Images

Figure SMS_1 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of heat insulation materials, and specifically relates to a heat reflective heat insulation coating and a preparation method thereof. Background Art
[0002] Heat reflective coatings can reflect the radiation energy of sunlight, and can play a role in heat insulation and cooling. They are important in aerospace, building wall insulation, road cooling, etc. Usually, fillers that can reflect visible light are added to the coating, such as rutile titanium dioxide, zinc oxide, barium sulfate, etc. These fillers can increase the heat reflectivity of the coating, thereby improving the thermal insulation performance.
[0003] Thermal insulation coatings have good thermal insulation properties and excellent thermal insulation properties. They are widely used in building materials, roads and bridges, cold storage transportation, etc. Adding materials with low thermal conductivity, such as cellulose aerogel, silica aerogel, etc., to the material can effectively reduce the thermal conductivity of the material and improve its thermal insulation properties. Patent CN116640546B discloses a thermal insulation and antibacterial polyurethane adhesive material and a preparation method thereof. Adding hyperbranched quaternary ammonium salt-modified cellulose aerogel to the polyurethane emulsion can improve the thermal insulation and antibacterial properties of the polyurethane adhesive. However, the patent does not improve the flame retardant properties of polyurethane. Adding flame retardants, such as ammonium polyphosphate, red phosphorus, phosphate (2-chloroethyl) triester, etc., to the polyurethane material is an effective method to improve its flame retardant properties, and compounding ammonium polyphosphate with a triazine carbonizing agent to form a synergistic flame retardant can further improve the flame retardant properties of the material. Summary of the invention
[0004] (I) Technical problems to be solved: The present invention solves the problems of poor thermal insulation performance and poor flame retardancy of polyurethane coatings.
[0005] (II) Technical solution: A heat-reflective heat-insulating coating, characterized in that the heat-reflective heat-insulating coating comprises 100 parts by weight of polyurethane, 15-40 parts by weight of titanium dioxide-loaded cellulose aerogel, 0.3-0.8 parts by weight of defoamer, 0.3-0.6 parts by weight of leveling agent, and 10-25 parts by weight of ammonium polyphosphate;
[0006] The preparation method of titanium dioxide loaded cellulose aerogel is as follows:
[0007] (1) Nanocellulose is oxidized by sodium periodate to obtain aldehyde-based nanocellulose; the aldehyde-based nanocellulose is then added to N,N-dimethylformamide, stirred and dispersed, 2-dopamine-4,6-diamino-1,3,5-triazine is added, ethanol is added to dilute after the reaction, filtered, washed with ethanol, and dried to obtain dopamine-triazine-modified nanocellulose.
[0008] (2) Add 100 parts by weight of dopamine triazine modified nanocellulose to water, stir and disperse in a high-speed shear emulsifier to obtain a nanocellulose solution; add 40-120 parts by weight of rutile nano-titanium dioxide to water, disperse by ultrasonic, then pour into the nanocellulose solution, stir for surface modification, then pour into a mold, freeze with liquid nitrogen, and finally freeze-dry in a freeze dryer to obtain titanium dioxide-loaded cellulose aerogel.
[0009] Preferably, in (1), the amount of aldehyde-based nanocellulose is 100 parts by weight, and the amount of 2-dopamine-4,6-diamino-1,3,5-triazine is 60-150 parts by weight.
[0010] Preferably, in (1), the reaction temperature is 70-90°C and the reaction time is 12-18h.
[0011] Preferably, in (2), the surface modification temperature is 20-40°C and the time is 12-24h.
[0012] Preferably, the preparation method of 2-dopamine-4,6-diamino-1,3,5-triazine is as follows: add 100 parts by weight of 2-chloro-4,6-diamino-1,3,5-triazine, 125-135 parts by weight of dopamine hydrochloride, 115-140 parts by weight of sodium bicarbonate, and water as a cosolvent to an ethanol solvent, condense and reflux at 75-85°C for 3-6 hours, and after the reaction, remove ethanol by vacuum distillation of the solution, add saturated sodium chloride solution and dichloromethane, combine the organic phases after extraction, dry and remove water, remove dichloromethane by vacuum distillation, and then recrystallize in ethanol to obtain 2-dopamine-4,6-diamino-1,3,5-triazine. The reaction formula is:
[0013]
[0014] Preferably, the amount of ethanol solvent used is 100 parts by volume, and the amount of water co-solvent used is 80-100 parts by volume.
[0015] Preferably, water-based polyurethane, titanium dioxide-loaded cellulose aerogel, defoamer, leveling agent, and ammonium polyphosphate are added to water, and the mixture is stirred and dispersed in a high-speed shear emulsifier to obtain a heat-reflective heat-insulating coating.
[0016] (III) Technical effect: The present invention utilizes the amino group of 2-dopamine-4,6-diamino-1,3,5-triazine to react with the aldehyde group of aldehyde-based nanocellulose to obtain dopamine triazine-modified nanocellulose, thereby introducing a catechol structure and a nitrogen-rich triazine ring structure into the nanocellulose molecular chain.
[0017] The present invention uses dopamine triazine modified nanocellulose as the matrix of the aerogel, and adds rutile nano titanium dioxide at the same time. Rutile nano titanium dioxide has a high refractive index and has a strong reflective effect on visible light. Dopamine triazine modified nanocellulose contains a large amount of catechol structure, which can coordinate with the titanium atom of nano titanium dioxide, thereby realizing the surface modification of nano cellulose on nano titanium dioxide, which is beneficial to improving the dispersibility of nano titanium dioxide, making the nano titanium dioxide uniformly dispersed in the cellulose aerogel matrix and the polyurethane coating, inhibiting the agglomeration of nano titanium dioxide, reducing the particle size of nano titanium dioxide, and making the particle size distribution of nano titanium dioxide meet the requirements of reflecting sunlight, thereby improving the thermal reflectivity and thermal reflection performance of the coating, and having better thermal reflection and heat insulation effects.
[0018] The cellulose aerogel of the present invention has a porous structure and poor thermal conductivity. When added to polyurethane coating, the heat conduction path of the polyurethane coating is destroyed, thereby reducing the thermal conductivity of the coating and improving the thermal insulation performance of the coating.
[0019] The cellulose aerogel of the invention contains a large amount of triazine nitrogen-rich functional groups, takes the triazine functional groups as the gas source, the cellulose aerogel matrix as the carbon source, and the ammonium polyphosphate as the acid source, to form an expansion flame retardant system, and forms a continuous expansion foam carbon layer on the surface of the polyurethane coating during combustion, which has the functions of isolating oxygen, preventing heat transfer, etc., and at the same time, the nano titanium dioxide in the aerogel also has a certain flame retardant effect, thereby improving the flame retardant performance of the coating, and having a lower combustion heat release rate peak value and total heat release. DETAILED DESCRIPTION
[0020] The technical scheme of the present invention is further illustrated by specific examples below. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0021] Waterborne polyurethane, brand 5136, Wuhan Shiquanxing New Materials Technology Co., Ltd.
[0022] Nanocellulose, model Darl-1, Hubei Darli Chemical Co., Ltd.
[0023] Rutile nano-titanium dioxide, brand TIMP4, particle size 100-200nm, Qinghe Chaotai Metal Materials Co., Ltd.
[0024] The defoaming agent is TEGO Foamex 810. The leveling agent is BYK-306.
[0025] Example 1
[0026] (1) Add 20 g of nanocellulose to 500 mL of water, stir and disperse in a high-speed shear emulsifier, then add 6.8 g of sodium periodate, heat to 50 ° C, react for 3 hours in the dark, add ethanol, centrifuge, wash with water, and dry to obtain aldehyde-based nanocellulose.
[0027] (2) Add 6g 2-chloro-4,6-diamino-1,3,5-triazine, 8.1g dopamine hydrochloride, 6.9g sodium bicarbonate, and 300mL water to 300mL ethanol, condense and reflux at 80°C for 6h, remove ethanol by vacuum distillation after the reaction, add saturated sodium chloride solution and dichloromethane, combine the organic phases after extraction, dry and remove water, remove dichloromethane by vacuum distillation, and then recrystallize in ethanol to obtain 2-dopamine-4,6-diamino-1,3,5-triazine. The structural formula is: .
[0028] (3) Add 20 g of aldehyde-based nanocellulose to 600 mL of N,N-dimethylformamide, stir and disperse, add 12 g of 2-dopamine-4,6-diamino-1,3,5-triazine, heat to 80 °C, react for 12 h, add ethanol to dilute, filter, wash with ethanol, and dry to obtain dopamine triazine modified nanocellulose.
[0029] (4) Add 30 g of dopamine triazine-modified nanocellulose to 3 L of water, stir and disperse in a high-speed shear emulsifier to obtain a nanocellulose solution; add 12 g of rutile nano-titanium dioxide to 2 L of water, ultrasonically disperse in an ultrasonic instrument, and then pour it into the nanocellulose solution, stir at 20 ° C for surface modification for 24 h, then pour it into a mold, freeze it with liquid nitrogen, and finally freeze-dry it in a freeze dryer for 48 h at a temperature of -55 ° C to obtain titanium dioxide-loaded cellulose aerogel.
[0030] (5) Add 1000 g of waterborne polyurethane, 150 g of titanium dioxide-loaded cellulose aerogel, 8 g of defoamer, 4 g of leveling agent, and 100 g of ammonium polyphosphate to 1200 mL of water, and stir and disperse in a high-speed shear emulsifier to obtain a heat-reflective thermal insulation coating.
[0031] Example 2
[0032] (1) Add 6 g of 2-chloro-4,6-diamino-1,3,5-triazine, 7.5 g of dopamine hydrochloride, 6.9 g of sodium bicarbonate, and 240 mL of water to 300 mL of ethanol, and reflux at 85°C for 3 h. After the reaction, distill the solution under reduced pressure to remove ethanol, add saturated sodium chloride solution and dichloromethane, extract, combine the organic phases, dry to remove water, dichloromethane is removed by distillation under reduced pressure, and then recrystallize from ethanol to obtain 2-dopamine-4,6-diamino-1,3,5-triazine.
[0033] (2) Add 20 g of aldehyde-based nanocellulose (prepared according to the method of Example 1) to 800 mL of N,N-dimethylformamide, stir and disperse, add 22 g of 2-dopamine-4,6-diamino-1,3,5-triazine, heat to 90°C, react for 12 h, add ethanol to dilute, filter, wash with ethanol, and dry to obtain dopamine triazine modified nanocellulose.
[0034] (3) Add 30 g of dopamine triazine-modified nanocellulose to 3 L of water, stir and disperse in a high-speed shear emulsifier to obtain a nanocellulose solution; add 24 g of rutile nano-titanium dioxide to 3 L of water, ultrasonically disperse in an ultrasonic instrument, and then pour it into the nanocellulose solution, stir at 40 ° C for 12 h for surface modification, then pour it into a mold, freeze it with liquid nitrogen, and finally freeze-dry it in a freeze dryer for 48 h at a temperature of -55 ° C to obtain titanium dioxide-loaded cellulose aerogel.
[0035] (4) Add 1000 g of waterborne polyurethane, 150 g of titanium dioxide-loaded cellulose aerogel, 8 g of defoamer, 3 g of leveling agent, and 180 g of ammonium polyphosphate to 1500 mL of water, and stir and disperse in a high-speed shear emulsifier to obtain a heat-reflective thermal insulation coating.
[0036] Example 3
[0037] (1) Add 6 g of 2-chloro-4,6-diamino-1,3,5-triazine, 7.8 g of dopamine hydrochloride, 8.4 g of sodium bicarbonate and 300 mL of water to 300 mL of ethanol, condense and reflux at 75°C for 5 h, and after the reaction, distill the solution under reduced pressure to remove ethanol. Add saturated sodium chloride solution and dichloromethane, extract and combine the organic phases, dry to remove water, dichloromethane is removed by distillation under reduced pressure, and then recrystallize from ethanol to obtain 2-dopamine-4,6-diamino-1,3,5-triazine.
[0038] (2) Add 20 g of aldehyde-based nanocellulose (prepared according to the method of Example 1) to 800 mL of N,N-dimethylformamide, stir and disperse, add 30 g of 2-dopamine-4,6-diamino-1,3,5-triazine, heat to 70°C, react for 18 h, add ethanol to dilute, filter, wash with ethanol, and dry to obtain dopamine triazine modified nanocellulose.
[0039] (3) Add 30 g of dopamine triazine modified nanocellulose to 3 L of water, stir and disperse in a high-speed shear emulsifier to obtain a nanocellulose solution; add 36 g of rutile nano-titanium dioxide to 4 L of water, ultrasonically disperse in an ultrasonic instrument, and then pour it into the nanocellulose solution, stir at 30 ° C for surface modification for 24 h, then pour it into a mold, freeze it with liquid nitrogen, and finally freeze-dry it in a freeze dryer for 48 h at a temperature of -55 ° C to obtain titanium dioxide-loaded cellulose aerogel.
[0040] (4) Add 1000 g of waterborne polyurethane, 150 g of titanium dioxide-loaded cellulose aerogel, 3 g of defoamer, 6 g of leveling agent, and 250 g of ammonium polyphosphate to 1500 mL of water, and stir and disperse in a high-speed shear emulsifier to obtain a heat-reflective thermal insulation coating.
[0041] Comparative Example 1
[0042] (1) Add 1000 g of waterborne polyurethane, 8 g of defoamer, 4 g of leveling agent, and 100 g of ammonium polyphosphate to 1200 mL of water, and stir and disperse in a high-speed shear emulsifier to obtain a heat-reflective thermal insulation coating.
[0043] Comparative Example 2
[0044] (1) Add 30 g of aldehyde-based nanocellulose (prepared according to the method of Example 1) to 3 L of water, stir and disperse in a high-speed shear emulsifier to obtain a nanocellulose solution; add 12 g of rutile nano-titanium dioxide to 2 L of water, ultrasonically disperse in an ultrasonic instrument, and then pour it into the nanocellulose solution, stir at 20°C for surface modification for 24 hours, then pour it into a mold, freeze it with liquid nitrogen, and finally freeze-dry it in a freeze dryer for 48 hours at a temperature of -55°C to obtain titanium dioxide-loaded cellulose aerogel.
[0045] (2) Add 1000 g of waterborne polyurethane, 150 g of titanium dioxide-loaded cellulose aerogel, 8 g of defoamer, 4 g of leveling agent, and 100 g of ammonium polyphosphate to 1200 mL of water, and stir and disperse in a high-speed shear emulsifier to obtain a heat-reflective thermal insulation coating.
[0046] Comparative Example 3
[0047] (1) Add 20 g of aldehyde-based nanocellulose (prepared according to the method of Example 1) to 600 mL of N,N-dimethylformamide, stir and disperse, add 12 g of dopamine hydrochloride, add 2.53 g of sodium hydroxide to neutralize and remove hydrochloric acid, heat to 80°C, react for 12 h, add ethanol to dilute, filter, wash with ethanol, and dry to obtain dopamine-modified nanocellulose.
[0048] (2) Add 30 g of dopamine-modified nanocellulose to 3 L of water, stir and disperse in a high-speed shear emulsifier to obtain a nanocellulose solution; add 12 g of rutile nano-titanium dioxide to 2 L of water, ultrasonically disperse in an ultrasonic instrument, and then pour it into the nanocellulose solution, stir at 20 ° C for surface modification for 24 h, then pour it into a mold, freeze it with liquid nitrogen, and finally freeze-dry it in a freeze dryer for 48 h at a temperature of -55 ° C to obtain titanium dioxide-loaded cellulose aerogel.
[0049] (3) Add 1000 g of waterborne polyurethane, 150 g of titanium dioxide-loaded cellulose aerogel, 8 g of defoamer, 4 g of leveling agent, and 100 g of ammonium polyphosphate to 1200 mL of water, and stir and disperse in a high-speed shear emulsifier to obtain a heat-reflective thermal insulation coating.
[0050] Thermal conductivity test: The curing temperature of the thermal insulation coating is 80℃ and the curing time is 10h. The coating with a thickness of 1mm is formed by thermal curing. The thermal conductivity of the coating is tested using a thermal conductivity meter.
[0051] Thermal reflectivity test:
[0052] (1) Black polyurethane paint (model polyurethane topcoat 55199, color RAL9004 signal black 17940) was evenly coated on the upper surface of the two aluminum plates. After curing, the coating thickness was controlled to be 0.3 mm, which was recorded as aluminum plate A. Take another aluminum plate and evenly coat the upper surface with heat-reflecting heat-insulating paint. After curing, the coating thickness was controlled to be 0.3 mm, which was recorded as aluminum plate B.
[0053] (2) Place two aluminum plates A on a polystyrene foam plate with the side coated with black polyurethane facing up. The edge distance between the two aluminum plates A is 50 mm and they are directly below the iodine tungsten lamp. Adjust the distance between the iodine tungsten lamp and the sample plate and the power supply voltage of the iodine tungsten lamp so that the surface temperature of the two aluminum plates A reaches equilibrium within 30 minutes. Record the equilibrium temperature T b .
[0054] (3) After the surface temperatures of the two aluminum plates A reach equilibrium, remove one aluminum plate A and replace it with another aluminum plate B (coated with heat-reflective insulation paint facing upwards). When the temperature reaches equilibrium again, measure the surface temperature T of aluminum plate B. x .
[0055] Calculate the thermal reflectivity P; P = (T b -T x ) / (T x -T n )×100%. T b is the equilibrium temperature of the aluminum plate A surface, which is measured to be 87.3°C. n The room temperature was 27.6°C. The test results are shown in Table 1 below.
[0056] Table 1 Thermal conductivity and thermal reflectivity test
[0057]
[0058] It can be seen from Table 1 that the thermal conductivity of Examples 1, 2, and 3 is only 0.125-0.148 W·m -1 ·K -1 The smaller the thermal conductivity, the better the thermal insulation performance. The thermal reflectivity reaches 59.1-62.9%. The greater the thermal reflectivity, the better the thermal reflectivity. This is because titanium dioxide-loaded cellulose aerogel is added to each embodiment. The cellulose aerogel has a porous structure and a very low thermal conductivity. When added to the polyurethane coating, the heat conduction path of the polyurethane coating is destroyed, thereby reducing the thermal conductivity of the coating and improving the thermal insulation performance of the coating. In addition, the refractive index of rutile nano-titanium dioxide is very high, and it has a strong reflective effect on visible light. Dopamine triazine-modified nano-cellulose contains a large amount of catechol structure, which can coordinate with the titanium atoms of nano-titanium dioxide, thereby realizing the surface modification of nano-cellulose on nano-titanium dioxide, which is beneficial to improve the dispersibility of nano-titanium dioxide, make the nano-titanium dioxide evenly dispersed in the cellulose aerogel matrix and the polyurethane coating, inhibit the agglomeration of nano-titanium dioxide, reduce the particle size of nano-titanium dioxide, and make the particle size distribution of nano-titanium dioxide meet the requirements of reflecting sunlight, thereby improving the thermal reflectivity and thermal reflection performance of the coating, and having better thermal reflection and heat insulation effects.
[0059] In Comparative Example 1, no titanium dioxide-loaded cellulose aerogel was added, the thermal conductivity of the coating was relatively large, the thermal reflectivity was low, and the thermal insulation performance and thermal reflection and heat insulation performance were relatively poor.
[0060] Comparative Example 2 uses aldehyde-based nanocellulose as the carrier of aerogel, which does not contain a catechol structure and cannot coordinate with nano-titanium dioxide, and cannot achieve surface modification of nano-titanium dioxide, resulting in poor dispersion of nano-titanium dioxide in the cellulose aerogel matrix, easy agglomeration and aggregation to form large particles, and does not meet the requirements of reflecting sunlight well, resulting in low thermal reflectivity of the coating and poor thermal reflection and insulation effects.
[0061] In Comparative Example 3, the amino group of dopamine hydrochloride is reacted with the aldehyde group of aldehyde-based nanocellulose. The obtained dopamine-modified nanocellulose also contains a catechol structure, which can coordinate with the titanium atom of nano-titanium dioxide, thereby realizing the surface modification of nano-titania by nanocellulose, which is beneficial to improving the dispersibility of nano-titanium dioxide in the cellulose aerogel matrix and the polyurethane coating, inhibiting the agglomeration of nano-titanium dioxide, thereby improving the thermal reflectivity and thermal reflective performance of the coating, and having better thermal reflective and heat-insulating effects.
[0062] The combustion performance of polyurethane coating was tested by cone calorimeter. The sample size was 100mm×50mm×1mm. The thermal radiation power was 35kW / m 2 The test results are shown in Table 2 below.
[0063] Table 2 Combustion performance test
[0064]
[0065] As can be seen from Table 2, the peak value and total heat release of the combustion heat release rate of Examples 1, 2, and 3 are lower than those of Comparative Examples 1, 2, and 3. This is mainly because in the examples, 2-dopamine-4,6-diamino-1,3,5-triazine is reacted with aldehyde-based nanocellulose to make the cellulose aerogel contain a large amount of triazine nitrogen-rich functional groups, which are used as gas sources, the cellulose aerogel matrix as a carbon source, and ammonium polyphosphate as an acid source to form an expansion flame retardant system. During combustion, a continuous expansion foam carbon layer is formed on the surface of the polyurethane coating, which has the effects of isolating oxygen and preventing heat transfer. At the same time, the nano titanium dioxide in the aerogel also has a certain flame retardant effect, thereby improving the flame retardant performance of the coating, and having a lower peak value and total heat release of the combustion heat release rate.
[0066] The cellulose aerogels of Comparative Examples 2 and 3 do not contain triazine nitrogen-rich functional groups, resulting in a large peak value of the combustion heat release rate and a large total heat release of the polyurethane coating, and poor flame retardant properties.
[0067] Example 4
[0068] (1) Add 1000 g of waterborne polyurethane, 190 g of titanium dioxide-loaded cellulose aerogel (prepared according to the method of Example 1), 8 g of defoamer, 4 g of leveling agent, and 100 g of ammonium polyphosphate to 1200 mL of water, and stir and disperse in a high-speed shear emulsifier to obtain a heat-reflective thermal insulation coating.
[0069] Example 5
[0070] (1) Add 1000 g of waterborne polyurethane, 230 g of titanium dioxide-loaded cellulose aerogel (prepared according to the method of Example 1), 8 g of defoamer, 4 g of leveling agent, and 100 g of ammonium polyphosphate to 1200 mL of water, and stir and disperse in a high-speed shear emulsifier to obtain a heat-reflective thermal insulation coating.
[0071] Example 6
[0072] (1) Add 1000 g of waterborne polyurethane, 320 g of titanium dioxide-loaded cellulose aerogel (prepared according to the method of Example 1), 8 g of defoamer, 4 g of leveling agent, and 100 g of ammonium polyphosphate to 1200 mL of water, and stir and disperse in a high-speed shear emulsifier to obtain a heat-reflective heat-insulating coating.
[0073] Example 7
[0074] (1) Add 1000 g of waterborne polyurethane, 400 g of titanium dioxide-loaded cellulose aerogel (prepared according to the method of Example 1), 8 g of defoamer, 4 g of leveling agent, and 100 g of ammonium polyphosphate to 1200 mL of water, and stir and disperse in a high-speed shear emulsifier to obtain a heat-reflective heat-insulating coating.
[0075] The thermal conductivity, thermal reflectivity and flame retardancy of the polyurethane coating were tested according to the above method. The test results are shown in Table 3 below.
[0076] Table 3 Thermal conductivity, thermal reflectivity and flame retardant performance tests
[0077]
[0078] In Examples 4-7, different amounts of titanium dioxide loaded cellulose aerogel were added, and the coatings all had lower thermal conductivity, combustion heat release rate peak, total heat release and higher thermal reflectivity, showing good thermal insulation, heat reflection insulation and flame retardant properties.
[0079] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A heat-reflective heat-insulating coating, characterized in that: The heat-reflective heat-insulating coating comprises 100 parts by weight of waterborne polyurethane, 15-40 parts by weight of titanium dioxide-loaded cellulose aerogel, 0.3-0.8 parts by weight of a defoamer, 0.3-0.6 parts by weight of a leveling agent, and 10-25 parts by weight of ammonium polyphosphate; The preparation method of the titanium dioxide-loaded cellulose aerogel is as follows: (1) Oxidizing nanocellulose with sodium periodate to obtain aldehyde-based nanocellulose; then adding the aldehyde-based nanocellulose to N,N-dimethylformamide, stirring and dispersing, adding 2-dopamine-4,6-diamino-1,3,5-triazine, adding ethanol to dilute after the reaction, filtering, washing, and drying to obtain dopamine-triazine-modified nanocellulose; (2) Add dopamine triazine modified nanocellulose to water, stir and disperse in a high-speed shear emulsifier to obtain a nanocellulose solution; add rutile nano-titanium dioxide to water, disperse by ultrasonic, then pour into the nanocellulose solution, stir for surface modification, then pour into a mold, freeze with liquid nitrogen, and finally freeze-dry in a freeze dryer to obtain titanium dioxide loaded cellulose aerogel.
2. The heat-reflective heat-insulating coating according to claim 1, characterized in that: In the above (1), the amount of aldehyde-based nanocellulose is 100 parts by weight, and the amount of 2-dopamine-4,6-diamino-1,3,5-triazine is 60-150 parts by weight.
3. The heat-reflective heat-insulating coating according to claim 1, characterized in that: In the above (1), the reaction temperature is 70-90°C and the reaction time is 12-18h.
4. The heat-reflective heat-insulating coating according to claim 1, characterized in that: In the above (2), the amount of dopamine triazine modified nanocellulose is 100 parts by weight, and the amount of rutile nano-titanium dioxide is 40-120 parts by weight.
5. The heat-reflective heat-insulating coating according to claim 1, characterized in that: In the above (2), the temperature during surface modification is 20-40°C and the time is 12-24h.
6. The heat-reflective heat-insulating coating according to claim 1, characterized in that: The preparation method of 2-dopamine-4,6-diamino-1,3,5-triazine comprises the following steps: adding 2-chloro-4,6-diamino-1,3,5-triazine, dopamine hydrochloride, sodium bicarbonate and water as a cosolvent to an ethanol solvent, and after the reaction, performing reduced pressure distillation on the solution, extracting and recrystallizing to obtain 2-dopamine-4,6-diamino-1,3,5-triazine.
7. The heat-reflective heat-insulating coating according to claim 6, characterized in that: The usage of the 2-chloro-4,6-diamino-1,3,5-triazine is 100 parts by weight, the usage of the dopamine hydrochloride is 125-135 parts by weight, and the usage of the sodium bicarbonate is 115-140 parts by weight.
8. The heat-reflective heat-insulating coating according to claim 6, characterized in that: In the preparation method of 2-dopamine-4,6-diamino-1,3,5-triazine, the reaction temperature is 75-85° C. and the reaction time is 3-6 hours.
9. The heat-reflective heat-insulating coating according to claim 6, characterized in that: The amount of the ethanol solvent is 100 parts by volume, and the amount of the water co-solvent is 80-100 parts by volume.
10. A method for preparing the heat-reflective heat-insulating coating according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: adding waterborne polyurethane, titanium dioxide loaded cellulose aerogel, defoamer, leveling agent and ammonium polyphosphate into water, stirring and dispersing the mixture in a high-speed shearing emulsifier to obtain a heat-reflecting heat-insulating coating.
Citation Information
Cited By
TPU (thermoplastic polyurethane) heat-insulating film as well as preparation method and application thereof
CN121293730A
TPU heat insulation film, preparation method and application
CN121293730B
